THE INFLUENCE OF FINANCIAL RATIO ON FINANCIAL PERFORMANCE IN CONSUMPTION GOODS COMPANIES LISTED ON THE BEI FOR THE 2018-2022 PERIOD - Muthya Fajar Riani; Ni Luh Putu Ayu Rediastuti S; Riski Putri Kusumaningsih; Raden Muhammad Jiddan Aziz (Publikasi Inspirasi Indonesia, 2024)
This research explores the influence of liquidity, solvency and profitability on the financial performance of manufacturing companies on the Indonesia Stock Exchange (BEI), especially in the consumer goods sector. Using multiple linear regression analysis, these variables are evaluated to understand their impact individually and simultaneously. The research results show that liquidity has a significant influence on financial performance, while solvency has no effect individually. Profitability, on the other hand, shows a positive and significant impact on a company's financial performance. These findings provide important insights for the management of consumer goods companies amidst market dynamics influenced by the pandemic and PPKM policies. Implementing a comprehensive financial strategy, optimizing liquidity, maintaining solvency and increasing profitability, is recognized as the key to a company's sustainability and competitiveness in a competitive business environment.